2019
DOI: 10.3389/fcimb.2019.00113
|View full text |Cite
|
Sign up to set email alerts
|

Magnaporthe oryzae CK2 Accumulates in Nuclei, Nucleoli, at Septal Pores and Forms a Large Ring Structure in Appressoria, and Is Involved in Rice Blast Pathogenesis

Abstract: Magnaporthe oryzae (Mo) is a model pathogen causing rice blast resulting in yield and economic losses world-wide. CK2 is a constitutively active, serine/threonine kinase in eukaryotes, having a wide array of known substrates, and involved in many cellular processes. We investigated the localization and role of MoCK2 during growth and infection. BLAST search for MoCK2 components and targeted deletion of subunits was combined with protein-GFP fusions to investigate localization. We found one CKa and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 37 publications
(45 reference statements)
6
36
0
Order By: Relevance
“…To aid in interpreting the results, we made a functional classification of the interacting proteins. The pulldown was, as expected based on our previous study, overrepresented for proteins known to be present in nucleoli and at septa (4).…”
supporting
confidence: 88%
See 3 more Smart Citations
“…To aid in interpreting the results, we made a functional classification of the interacting proteins. The pulldown was, as expected based on our previous study, overrepresented for proteins known to be present in nucleoli and at septa (4).…”
supporting
confidence: 88%
“…Identification of potential septal and nucleolar and other substrates for MoCK2 by GFP-CKa pulldown and investigation of whether these proteins contain a CK2 phosphorylation unfolding motif. The CK2 localization pattern suggested that CK2 may have substrates associated with septa and nucleolar function (4). To explore this, we performed coimmunoprecipitation to identify proteins interacting with CK2, using GFP-CKa as a bait, and, in addition to the bait, identified 1,505 proteins (Data Set S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant pathogens have until now had little representation in these databases. Electronic resources for Fusarium graminearum eFG (Liu et al, 2013) a model species in plant pathology (Zhang et al, 2019), contains functional annotation as well as annotations of transcription factors and curated and predicted pathogenic genes for fusarium. PHI-base (Urban et al, 2017) is a great resource for curated Pathogen-Host Interactions but is manually curated and thus limited in size.…”
Section: Introductionmentioning
confidence: 99%